On the optical flow model selection through metaheuristics - Pereira, Danillo R. [UNESP]; Delpiano, José; Papa, João P. [UNESP] (Springer, 2015)
Optical flow methods are accurate algorithms for estimating the displacement and velocity fields of objects in a wide variety of applications, being their performance dependent on the configuration of a set of parameters. Since there is a lack of research that aims to automatically tune such parameters, in this work, we have proposed an optimization-based framework for such task based on social-spider optimization, harmony search, particle swarm optimization, and Nelder-Mead algorithm. The proposed framework employed the well-known large displacement optical flow (LDOF) approach as a basis algorithm over the Middlebury and Sintel public datasets, with promising results considering the baseline proposed by the authors of LDOF.
Keywords: Optimization methods; Evolutionary algorithms; Optical flow methods